EFEKTIVITAS PELATIHAN PEMBUATAN PMT MODISCO TERHADAP PENGETAHUAN IBU DI KELURAHAN TANJUNGREJO KECAMATAN SUKUN KOTA MALANG - Yeni Susanti; Mazarina Devi; Septa Katmawanti (Preventia : The Indonesian Journal of Public Health, 2018)
Abstract: Modisco (Modified Dietetic Skim and Cotton Sheet Oil) is an additional food that contains high calories to increase the children's weights. The procedure to make PMT modisco is very easy because it consists of three basic ingredients which are skim milk, sugar and margarine. This study aims to know the effect of the training to the mother knowledge in making PMT modisco, the training was done by using lecture and demonstration method. The research design used is pre-experimental by using one group pretest and posttes method. The data for knowledge used questionnaire while the data. The samples in this study were all of the mothers who have Bawah Garis Merah (BGM) children in the village of Tanjungrejo Sub-district of Sukun District of Malang that were 11 people. The result is knowledge data using paired samplet t-test that obtained the score of Sig. (2-tailed) was 0.000 < 0.05 which means there is the effectiveness of training to the mothers’ knowledge related to PMT modisco. The procedure of making module PMT is not too difficult, there are three basic ingredients modisco in training abbreviated with milk, sugar, and margarine (SGM). Keywords: Training, Knowledge, PMT ModiscoAbstrak: Modisco (Modified Dietetic Skim and Cotton Sheet Oil) merupakan makanan tambahan yang mengandung kalori tinggi untuk meningkatkan berat badan anak. Prosedur pembuatan PMT modisco sangat mudah karena terdiri dari tiga bahan dasar yaitu susu skim, gula dan margarine. Penelitian ini bertujuan untuk mengetahui pengaruh pelatihan terhadap pengetahuan Ibu tentang PMT modisco, pelatihan dengan metode ceramah dan demonstrasi. Jenis penelitian ini adalah pre-eksperimental dengan menggunakan desain one group pretest and posttest. Data pengetahuan menggunakan kuesioner, sampel penelitian ini adalah seluruh Ibu yang mempunyai anak Bawah Garis Merah (BGM) di Kelurahan Tanjungrejo Kecamatan Sukun Kota Malang sebanyak 11 orang. Hasil data pengetahuan menggunakan paired samplet t-test diketahui bahwa nilai Sig. (2-tailed) sebesar 0,000 < 0,05 artinya terdapat keefektivitasan pelatihan terhadap pengetahuan Ibu terkait PMT modisco. Prosedur pembuatan PMT modisco dirasa tidak terlalu susah, ada  tiga bahan dasar modisco yang dalam pelatihan disingkat dengan susu, gula, dan margarine (SGM).Kata kunci: Pelatihan, Pengetahuan, PMT Modisco